PENGEMBANGAN BUKU CERITA ANAK BERBASIS KULTUR BANJAR UNTUK MENINGKATKAN LITERASI BUDAYA SISWA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN 102052 BAGAN KUALA - Rahmadani; Sutarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Several problems were found at SDN 102052 Bagan Kuala, including that at the school only normal reading books were available, teachers only used teacher books and student books, lack of use and utilization of technology in the learning process, lack of students' understanding of Banjar culture and culture, and low students' cultural literacy level, especially Banjar culture. This research was carried out with the aim of finding out the suitability of the book, developing the book to find out students' cultural literacy and students' responses after using the Banjar Culture Based Children's Storybook. The research method used is the development method with the EDDIE model which consists of: Analysis, Design, Development, Implementation and Evaluation. The sample for this research was 30 class V students at SDN 102052 Bagan Kuala. There are 4 questionnaires used, namely: media validation questionnaire, material validation questionnaire, learning questionnaire and student response questionnaire. So it can be concluded that the Banjar Culture Based Children's Story Book, after the revision and validation process, states that the average percentage of eligibility for the Banjar Culture Based Children's Story Book is 85% in the "Very Eligible" category. Based on the suitability of the media from input from media experts, material experts and learning experts, namely class V teachers, the development of a Banjar Culture Based Children's Storybook developed by researchers was declared Very Suitable for use as teaching material in the learning process.